INTERVENTIONAL CARDIOLOGY: AN OVERVIEW OF CURRENT APPLICATIONS, CHALLENGES, AND FUTURE PATHWAYS – THE ERA OF AI-ASSISTED PCI? - Kamil Jabłoński; Aleksandra Grygorowicz; Klaudia Baran; Michał Ględa; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Karolina Nowacka; Anna Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Background: Interventional cardiology, which began in 1977, has evolved from primitive balloon angioplasty to sophisticated drug-eluting stents, fundamentally altering the treatment of coronary artery disease. We have reached a plateau in stent performance, where successive generations do not bring spectacular leaps forward. Consequently, the focus is shifting away from finding a universal gold standard toward a tailored, patient-specific approach that integrates a variety of revascularization strategies.Methods: A comprehensive search was conducted in the PubMed, Scopus, and IEEE Xplore databases to identify relevant publications from January 2005 to October 2025. The search strategy employed combinations of the following keywords: “Percutaneous Coronary Intervention”, “Fractional Flow Reserve”, “Intravascular Ultrasound”, “Artificial Intelligence”, “Optical Coherence Tomography”, “Coronary Artery Disease” and “Regulation”Results: Interventional cardiology is moving away from purely mechanical innovations toward a future defined by information integration, advanced visualization, and data-driven procedures. However, widespread implementation faces significant obstacles: difficulties in scaling technology, funding constraints, and complex legal requirements for data collection for artificial intelligence algorithms.Conclusion: It appears that despite regulatory and economic challenges, the field is inevitably moving from an era of simple tools to true partners, slowly considering at least partial autonomy in decision-making.